ANALISIS SIMULASI UPAYA MITIGASI GAS METAN PADA PADI SAWAH DI INDONESIASIMULATION ANALYSIS OF APPROACH ON MITIGATION OF METHANE GAS EMISSION RICE FIELDS IN INDONESIA - Sobri Effendy; I. Handoko; RTM Sutamihardja; Rokhmin Dahuri (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1997)
Abstract is available in the full text (pdf format)